Does Kangaroo Care Have an Effect on Transition Time from Gavage Feeding to Full Oral Feeding in Premature Babies? - Simsek, Didem Coskun; Aydin, Mustafa; Guenay, Ulviye (Georg Thieme Verlag Kg, 2023)
Objectives Kangaroo care is a safe and effective alternative method to conventional neonatal care for newborn babies. The aim of this study was to evaluate the effect of kangaroo care on the transition time to full oral feeding in preterm infants fed by gavage.Methods This is a randomized controlled trial. This study was conducted in a level III neonatal intensive care unit of a university hospital in eastern Turkey 50 premature babies with a birth weight of & GE;1000 g and a gestational age of 27-36 weeks, and their mothers were included in the study. The cases were randomly divided into two groups: kangaroo care, which would be applied up to five days a week, and standard care. Records of cases were kept regularly from their hospitalization until they reached full oral feeding.Results Premature babies in the kangaroo care group reached full oral feeding at 29.20 +/- 8.06 days after birth, while babies in the standard care group reached full oral feeding at 44.60 +/- 21.90 days. The transition period from gavage feeding to reaching full oral feeding was 13.60 +/- 6.83 days in the kangaroo care group, and 22.10 +/- 7.38 days in the standard care group. The difference was statistically significant (p = 0.007).Conclusion Kangaroo care is an effective method to reduce the transition time from gavage feeding to full oral feeding for premature babies.
Keywords: gavage feeding; kangaroo care; oral feeding; preterm babies